2019
DOI: 10.1111/dom.13648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SGLT2 inhibitors on cardiovascular, renal and safety outcomes in patients with type 2 diabetes mellitus and chronic kidney disease: A systematic review and meta‐analysis

Abstract: Aim The use of sodium glucose co‐transporter 2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) has been limited, primarily because glycaemic efficacy is dependent on kidney function. We performed a systematic review and meta‐analysis to assess the efficacy and safety of SGLT2 inhibitors in patients with T2DM and CKD, defined as estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2. Materials and methods We searched MEDLINE, EMBASE and the Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
191
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(213 citation statements)
references
References 106 publications
(156 reference statements)
18
191
0
4
Order By: Relevance
“…This finding reflects the mechanism for normal homeostatic regulation, which modulates glucose production and disposal to maintain stable serum glucose concentrations, despite urinary glucose loss. This observation also reflects the mechanism of action for rongliflozin, which is independent of insulin but dependent on filtered glucose load, suggesting a low propensity for causing hypoglycaemia …”
Section: Discussionmentioning
confidence: 60%
“…This finding reflects the mechanism for normal homeostatic regulation, which modulates glucose production and disposal to maintain stable serum glucose concentrations, despite urinary glucose loss. This observation also reflects the mechanism of action for rongliflozin, which is independent of insulin but dependent on filtered glucose load, suggesting a low propensity for causing hypoglycaemia …”
Section: Discussionmentioning
confidence: 60%
“…Although the ADVANCE study clearly demonstrated renoprotection with intensified glycaemic control using a sulphonylurea‐based regimen, this trial was completed before the widespread use and clinical investigation of newer glucose‐lowering agents, which may improve the outlook of diabetic kidney disease . These include sodium‐glucose co‐transporter‐2 inhibitors and glucagon‐like peptide‐1 receptor agonists which have been shown to confer end‐organ protection, at least in part via glucose‐independent mechanisms . Dipeptidyl peptidase‐4 (DPP‐4) inhibitors appear to be neutral in terms of cardiovascular protection .…”
Section: Perspectivesmentioning
confidence: 99%
“…Trial‐level analyses support a role for early change in albuminuria as a surrogate endpoint for progression of CKD in clinical trials; in patients with high baseline albuminuria the decrease of albuminuria of 30% might be considered as a surrogate endpoint for progression of CKD . In a meta‐analysis of RCTs to assess the efficacy and safety of SGLT‐2is in patients with T2D and DKD (eGFR <60 mL/min/1.73 m 2 ), SGLT‐2is can reduce albuminuria by 23%.…”
Section: Sglt‐2 Inhibitorsmentioning
confidence: 99%